Three Different Involvements in a Case of Ulcerative Colitis: Bilateral Femoral Head Avascular Necrosis, Spondylodiscitis and Spondyloarthropathy - Erdem Sultanoğlu, Tuba; Uçar Meydan, Sümeyye (Turkish journal of osteoporosis, 2025)
[LANGUAGE=”English”]Avascular necrosis (AVN) is a serious condition that develops as a result of inadequate blood supply to bone tissue. This condition is usually associated with trauma, long-term steroid use, or systemic diseases. Spondylodiscitis is a serious infection affecting the spinal discs and vertebral bodies and is usually of bacterial origin. The association of spondylodiscitis and avascular necrosis is rare. In this case report, bilateral femoral head avascular necrosis and spondylodiscitis coexistence in a 53-year-old female patient diagnosed with ulcerative colitis is discussed. This case aims to emphasize the risk of developing AVN and spondylodiscitis in patients with chronic inflammatory disease who receive long-term corticosteroid treatment.[LANGUAGE=”Turkish”]Avasküler nekroz (AVN), kemik dokusunun yetersiz kanlanması sonucu gelişen ciddi bir durumdur. Bu durum genellikle travma, uzun süreli steroid kullanımı veya sistemik hastalıklarla ilişkilidir. Spondilodiskit, omurga diskleri ve vertebra cisimlerini etkileyen ciddi bir enfeksiyon olup genellikle bakteriyel kaynaklıdır. Spondilodiskit ve AVN’nin birlikteliği nadir görülür. Bu olgu sunumunda, ülseratif kolit tanısı olan 53 yaşındaki kadın hastada bilateral femur başı AVN’yi ve spondilodiskit birlikteliği ele alınmıştır. Bu olgu, kronik inflamatuvar hastalığı olan, uzun süreli kortikosteroid tedavisi gören hastalarda AVN ve spondilodiskit gelişme riskinin vurgulanmasını amaçlamaktadır.Anahtar Kelimeler: